PENGARUH PENERAPAN METODE MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DALAM MATA PELAJARAN EKONOMI (Studi Kuasi Eksperimen pada Peserta Didik Kelas XI IIS SMA Negeri 1 Cililin) - Giri Aji Ramadhan, - (2019)
This research is motivated by the low creative thinking ability of students' class of XI IIS in SMA Negeri 1 Cililin as evidenced by the results of tests of creative thinking skills that are still in the low category. This study aims to determine the effect of applying mind mapping learning methods on students' creative thinking abilities in economic subjects with KD international economic cooperation material. The subjects in this study were students of class of XI IIS in SMA Negeri 1 Cililin. This study uses a Quasi-Non-Equivalent Control Group Design experimental method. Data analysis techniques with parametric statistics which include normality test, homogeneity test, and hypothesis test (paired sample t-test and independent sample t-test). This research instrument is in the form of description, the results of this study indicate: (1) There are differences in the creative thinking abilities of students in the experimental class before and after treatment with mind mapping and control class learning methods that use conventional learning methods (lectures) after being given treatment; (2) There is an increase in the creative thinking ability of experimental students with an N-Gain of 0.59 and an N-Gain of the control class of 0.31, both included in the medium category. The implication of this study is that teachers should use the mind mapping method as an alternative learning method that can be used in the learning process because the mind mapping method is effective in increasing students' creative thinking abilities compared to lectures method. Moreover, this method is one of the methods that support learning during the 2013 curriculum where students become the center of the learning process (student centered).